THE ANALYSIS OF FACTORS WHICH AFFECTING THE ACCEPTANCE OF GOING CONCERN OPINION - Rizca Anna Savitri; Denny Mahendra (STIE AUB Surakarta, 2018)
The purpose of this study is to analyze and show the empirical evidence that bankruptcy, company’s growth; firm size, prior year audit opinion, and opinion shopping have significant effect on acceptance going concern audit opinion. The population on this study was manufacturing companies listed on Indonesian Stock Exchange (BEI) in 2012 until 2016. Sample was determined by the method of purposive sampling. The data were secondary data that were obtained from www.idx.co.id. Analytical technique in the research consists of goodness of fit test, overall model fit, determination coefficient, and logistic regression for data analysis. The result showed that bankruptcy, firm size, and prior year audit opinion have significant effect on acceptance going concern audit opinion. Company growth and opinion shopping have no significant effect on acceptance going concern audit opinion. Nagelkerke R square results obtained results of 0,754 which means the variability of dependent variable able to explain by independent variables equal to 75,4% while the rest 24,6% explained by other variable not participated observed.Keywords: Banckruptcy, company size, Company growth, prior audit opinion, opinion shopping, going concern opinion